2017
DOI: 10.1136/bcr-2017-219527
|View full text |Cite
|
Sign up to set email alerts
|

Small cell lung cancer presenting as unilateral rhinorrhoea

Abstract: The metastatic spread of infraclavicular malignancies to the nasal cavity is rare. We describe the case of a 58-year-old man who presented with a 4-month history of right-sided rhinorrhoea, maxillary hypoesthesia, hyposmia and hypogeusia. Clinical examination revealed an irregular mass within the right nasal cavity. Immunohistochemical analyses of biopsies were consistent with small cell carcinoma of indeterminate origin. A positron emission tomography scan demonstrated extensive mediastinal lymphadenopathy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…On further workup, he was subsequently diagnosed with small-cell carcinoma of the lung. 3 Similarly, squamous cell carcinoma of the lung has also been reported to present as a nasal-tip mass growing more than a 3-month interval. 4 Huang et al have reported metastatic spread to paranasal sinus along with a literature review of similar cases.…”
Section: Discussionmentioning
confidence: 99%
“…On further workup, he was subsequently diagnosed with small-cell carcinoma of the lung. 3 Similarly, squamous cell carcinoma of the lung has also been reported to present as a nasal-tip mass growing more than a 3-month interval. 4 Huang et al have reported metastatic spread to paranasal sinus along with a literature review of similar cases.…”
Section: Discussionmentioning
confidence: 99%